Socio-environmental tensions and expansion of the extractive frontier: the case of the policy of protection of the PIACI in the Camisea Project - Mejía Tarazona, Alejandro (2019)
The advance of extractivism in Latin America after the boom of commodities has put on the public agenda the problem of the increase of socio-environmental conflicts in the Amazon, in a complex context of renewed disputes between the State, companies and indigenous peoples. This article addresses the discussion between public policy and state responsibility for the case of indigenous peoples in isolation and initial contact in the Camisea Project. The main argument is that, although the Peruvian State has innovated in the design of policies for the protection of the PIACIs, the existence of a diffuse institutional framework has allowed the emergence of socio-environmental conflicts due to the expansion of extractive borders and effects of fundamental, social and collective rights. This work is positioned in a context of increased socio-environmental tensions resulting from the increase of extractive activities in Camisea.